SYNTHESIS OF THE SOCIAL SANCTIONS MODEL FOR ENSURING THE SUSTAINABILITY OF VIRTUAL COMMUNITIES IN SOCIAL NETWORKS IN THE CONDITIONS OF AN ANTAGONISTIC ENVIRONMENT - Yevseiev, Serhii; Tymonin, Yuriy; Veretiuk, Serhiy; Voitko, Tetiana; Oleniuk, Dmytro (Ukrainian Information Security Research Journal, 2023)
The rapid integration of virtual communications into social life actualizes the need to create a safe and comfortable environment for the communication of virtual community users. The purpose of the study is to increase the level of information security of social virtual groups by substantiating and formalizing the features of using social control tools to manage the dynamics of the virtual community in the information space. The process of the virtual community evolution in the conditions of an antagonistic environment, as well as the functionality of management and ensuring the stability of the virtual community in social Internet services were formalized on the basis of Mono model and population dynamics model. The impact of the share of destructive publications that pose a threat to information security of the social community; the depth of communication between the actors of the studied community and the participants of the antagonistic community; content quality indicators were determined as the parameters of the author’s model. The components of social control in social Internet services and the classification of violators of information security were further developed.